RECTRACTED: Dividend Policy and Economic Variable to Stock Price Volatility: Comparison of Indonesia and Malaysia - Harlina, Vega Rut; Khoiruddin, Moh. (The Asian Journal of Technology Management (AJTM), 2019)
After publication of the article in the Asian Journal of Technology and Management (AJTM) journal, volume 12, number 3, in 2019, it came to the editors attention that the original article has been published in Management Analysis Journal (MAJ), volume 7, number 4, in 2018.Although the authors acknowledged that there is possibility of misunderstanding with the MAJ, the editors of AJTM see this practice as an example of neglecting the ethical procedure in academic work as all authors should understand.Due to the high potency of double-publication practice, the editors agreed to revoke the publication right of the article entitled Dividend Policy and Economic Variable to Stock Price Volatility: Comparison of Indonesia and Malaysia written by Vega Rut Harlina and Moh. Khoiruddin, affiliated to the Universitas Negeri Semarang, Indonesia.Considering this practice, the authors now blacklisted from submitting their work to AJTM journal. The author will not be able to submit the article to our journal for the next 12 monthsThe document and its content has been removed from the Asian Journal of Technology and Management (AJTM) and reasonable effort should be made to remove all references to this article.